Mrs. Lilly is silly! - Gutman, Dan.; Paillot, Jim. (New York : Scholastic, 2011)
On Career Day at Ella Mentry School, local reporter Mrs. Lilly helps A.J. and his fellow third-graders start a school newspaper, but their efforts have unexpected, and terrible, consequences.
"This edition is available for distribution only through the school market"--[P. 4] of cover.
540
Accelerated Reader AR
Keywords: Newspapers -- Juvenile fiction; Reporters and reporting -- Juvenile fiction; Schools -- Juvenile fiction